Kinectics of the Oxidation via Enalozation of Di-Ethylester of Ethyl Malonic Acid by Ceric Sulphate in Sulphuric Acid - Rawat, Kalpna; Verma, Sharda; Tandon, V.K. (Asian Journal of Chemistry, 2010)
The rate of bromination with respect to diethyl ester of ethyl malonic acid, bromine and hydrogen ion concentration is one, zero and one respectively, while the rate of oxidation is first order with respect to all the cerium (IV), diethyl ester of ethyl malonic acid and hydrogen ions. It was confirmed that the oxidation proceeds through enol form of ester, as the rate of bromination was found to be 1.35 times faster than the rate of oxidation. The energies for activation for bromination and oxidation were obtained to be 62.90 and 67.67 KJ mole–1, respectively. A mechanism of oxidation involving enol forms of the ester has been proposed.